Perancangan dan Implementasi Standard Operating Procedure (SOP) untuk Meningkatkan Mutu Pascapanen Jahe (Zingiber officinale) dengan Metode PDCA - Ikhsan Taat Tri Wijayanto; Nur Rohmah Lutfi A'yuni; Adi Prayoga (PAKIS JOURNAL INSTITUTE, 2026)
The SOP was developed based on the PDCA method by referring to the 2011 Guidelines for Post-Harvest Handling Technology of Medicinal Plants issued by the Ministry of Agriculture and the 2015 Guidelines for Post-Harvest Handling of Medicinal Plants issued by the Ministry of Health. This study aimed to implement the Plan-Do-Check-Act (PDCA) method in the design of a Standard Operating Procedure (SOP) for post-harvest handling of ginger (Zingiber officinale) to improve the quality of ginger simplicia at Sabda Rempah MSME. This study used a one-factor completely randomized design (CRD), namely drying temperature and duration, consisting of four treatments: 70 °C for 6 h, 40 °C for 9 h, 50 °C for 9 h, and 60 °C for 9 h. Each treatment was repeated three times, resulting in 12 experimental units. The differences between ginger post-harvest handling with and without SOP implementation were found in the wet sorting, draining, and dry sorting stages. The results showed differences in moisture content between ginger simplicia processed with and without the SOP. Ginger simplicia processed using the SOP had a moisture content of 9.47%, whereas ginger simplicia processed without the SOP had a moisture content of 13.86%. Sensory evaluation showed that ginger simplicia processed with the SOP had better color, aroma, and texture than those processed without the SOP. Moisture content data were analyzed using ANOVA, followed by Duncan’s Multiple Range Test (DMRT) when significant differences were found. In addition, a paired samples t-test was used to compare moisture content between the treatment without SOP at 70 °C for 6 h and the treatment with SOP at 60 °C for 9 h. The implementation of a PDCA-based SOP was proven to improve the quality of ginger simplicia.